Respostas
respondido por:
2
Método de adição
x+y=2 (-1)
2x+y=4
-x - y = -2
2x + y = 4
x = 2
x+y=2
2 + y = 2
y = 2 - 2
y = 0
Resposta :
x = 2
y = 0
x+y=2 (-1)
2x+y=4
-x - y = -2
2x + y = 4
x = 2
x+y=2
2 + y = 2
y = 2 - 2
y = 0
Resposta :
x = 2
y = 0
respondido por:
1
isola uma variável da primeira:
y=2-x
substitui na segunda:
2x+2-x=4
resolve a segunda:
x+2=4
x=4-2
x=2
substitui na primeira:
2+y=2
y=2-2
y=0
y=2-x
substitui na segunda:
2x+2-x=4
resolve a segunda:
x+2=4
x=4-2
x=2
substitui na primeira:
2+y=2
y=2-2
y=0
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás